TEMPERATE POOL WITH THE SUN ENERGY - Pacheco Luján, Werner (2004)
This article deals with the technical details for the building of a temperate pool with Sun collectors. The so called "tornillo" timber and the CPC Technology (composite parabolic collector) were used for. In the coonections, was to simplify outer ways intent to diminish heat loss. Eight collecting boxes were used with reflectors of shining aluminum foils were used. The purpose is to show a cheaper economical and ecological alternative for users.